Multi-modal sleep intervention for community-dwelling people living with dementia and primary caregiver dyads with sleep disturbance: protocol of a single-arm feasibility trial - Verma,Sumedha; Varma,Prerna; Brown,Aimee; Bei,Bei; Gibson,Rosemary; Valenta,Tom; Pietsch,Ann; Cavuoto,Marina; Woodward,Michael; McCurry,Susan; Jackson,Melinda L. (PeerJ, 2023)
Background Disturbed sleep is common among people living with dementia and their informal caregivers, and is associated with negative health outcomes. Dyadic, multi-modal interventions targeting caregiver and care-recipient sleep have been recommended yet remain limited. This protocol details the development of a single-arm feasibility trial of a multi-modal, therapist-led, six-week intervention targeting sleep disturbance in dyads of people living with dementia and their primary caregiver. Methods We aim to recruit 24 co-residing, community-dwelling dyads of people living with dementia and their primary informal caregiver (n = 48) with sleep concerns (Pittsburgh Sleep Quality Index ≥5 for caregivers, and caregiver-endorsed sleep concerns for the person living with dementia). People who live in residential care settings, are employed in night shift work, or are diagnosed with current, severe mental health conditions or narcolepsy, will be excluded. Participants will wear an actigraph and complete sleep diaries for two weeks prior, and during the last two weeks, of active intervention. The intervention is therapist-led and includes a mix of weekly small group video sessions and personalised, dyadic sessions (up to 90 min each) over six weeks. Sessions are supported by a 37-page workbook offering strategies and spaces for reflections/notes. Primary feasibility outcomes are caregiver: session attendance, attrition, and self-reported project satisfaction. Secondary outcomes include dyadic self-reported and objectively-assessed sleep, depression and anxiety symptoms, quality of life, and social support. Self-report outcomes will be assessed at pre- and post-intervention. Discussion If feasible, this intervention could be tested in a larger randomised controlled trial to investigate its efficacy, and, upon further testing, may potentially represent a non-pharmacological approach to reduce sleep disturbance among people living with dementia and their caregivers. ANZCTR Trial registration ACTRN12622000144718: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=382960&showOriginal=true&isReview=true
Keywords: Dementia; Caregivers; Insomnia; Cognitive behavioural therapy; Intervention; Feasibility